La seconde patrie of a Basel Missionary: Inscription, Inclination, and Initiative in the Life of Edmond Perregaux among the Akan - McCaskie, T.C. (Journal of religion in Africa, 2017)
This paper explores the life of the Basel missionary Edmond Perregaux (1868-1905) in Switzerland and among the Akan of Ghana. It is concerned with the construction and expression of his selfhood in and between two different worlds in the later nineteenth century under the aegis of an ever advancing globalization. In brief, the paper looks at a Swiss missionary as an actor in Africa and among Africans and reflects upon the matter of reconciling and integrating these two arenas of experience in the formation of his individual subjectivity. It is aimed at creating a much needed bridge between the discrete concerns of Missionary and Africanist historians, and to suggest within the framework of a single individual life the possibilities for a richer, more textured understanding of personhood when all due attention is paid to the interactions between the shaping environments of both home and abroad.